2016
DOI: 10.1073/pnas.1607580113
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine deamination and the precipitous decline of spontaneous mutation during Earth's history

Abstract: The hydrolytic deamination of cytosine and 5-methylcytosine residues in DNA appears to contribute significantly to the appearance of spontaneous mutations in microorganisms and in human disease. In the present work, we examined the mechanism of cytosine deamination and the response of the uncatalyzed reaction to changing temperature. The positively charged 1,3-dimethylcytosinium ion was hydrolyzed at a rate similar to the rate of acid-catalyzed hydrolysis of 1-methylcytosine, for which it furnishes a satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 43 publications
(32 reference statements)
1
52
1
Order By: Relevance
“…The formation of uracil and thymine from the spontaneous hydrolytic deamination of cytosine and 5-methylcytosine, respectively 1,2 occurs an estimated 100–500 times per cell per day in humans 1 and can result in C•G to T•A mutations, accounting for approximately half of all known pathogenic SNPs (Fig. 1a).…”
mentioning
confidence: 99%
“…The formation of uracil and thymine from the spontaneous hydrolytic deamination of cytosine and 5-methylcytosine, respectively 1,2 occurs an estimated 100–500 times per cell per day in humans 1 and can result in C•G to T•A mutations, accounting for approximately half of all known pathogenic SNPs (Fig. 1a).…”
mentioning
confidence: 99%
“…The 50,000 lesions produced per cell per day as a result of spontaneous and/or endogenous chemical reactions [1] are not localized to specific genes but instead are distributed stochastically. Important sources of DNA damage include the chemical instability of the DNA helix by depurination [1, 26–27], deamination of cytidine to thymidine [28], and by cellular reactive molecules (eg, oxygen and nitrogen reactive species) [29]. Damage by environmental agents frequently involves similar chemical alterations, and in order to be a significant cause of human cancer must contribute a comparable number of lesions.…”
Section: Experimental Support For the Mutator Phenotype Hypothesismentioning
confidence: 99%
“…At both ambient and high pressures, the half-life of cytosine decreases significantly as the pH decreases from 7.0 to 6.0. These studies have been augmented very recently by Lewis et al, [12] who reported rate constantsa nd an enthalpy of activation of about 23 kcal mol À1 for the deamination of cytosine andv arious derivatives at pH 2.4 and 7.0 over the temperature range from about 90 to 200 8C.Assuming that earliest life-forms werer ather inefficient and not adapteda nd stripped down for speedy turnover,i nc ontrast to many extant Prokarya and Archaea, these results on the diminished chemical stabilityo fc ytosine at elevated temperatures and the physicali nstability of folded RNA structures have rendered unlikely ah ot-starts cenario for RNA-basedl ifeforms. Many scenarios have RNA-based lifeforms preceding the extant protein-based life-forms, [1] or coevolution of RNA alongside DNA.…”
mentioning
confidence: 91%
“…As ingle point of agreement in current( i.e.,s ince % 2012) origin-of-life scenarios invokesar ole for FeS species in redox reactions. These studies have been augmented very recently by Lewis et al, [12] who reported rate constantsa nd an enthalpy of activation of about 23 kcal mol À1 for the deamination of cytosine andv arious derivatives at pH 2.4 and 7.0 over the temperature range from about 90 to 200 8C. [8] With respectt oc hemi-cal stability,s tudies under mesophilic conditions have revealed the susceptibility of cytosine and cytidine to hydrolytic deamination, [9] both as individual molecules and upon incorporation into about 5000 base-pair bacteriophage DNA.…”
mentioning
confidence: 91%
See 1 more Smart Citation